Thr Usage Comparison of Chloramphenicol and Levofloxacin as Therapy for Bacterial Conjunctivitis - Alfina Indah Nabila; yusran; rasmi zakiah oktarlina (CV. Jasa Sukses Abadi, 2021)
Conjunctivitis is one of the most common eye diseases. Bacterial conjunctivitis ranks second after viral conjunctivitis as the most common cause of infectious conjunctivitis. Bacterial conjunctivitis can affect anyone of all ages, both men and women. One of the non-gonococcal bacteria that often causes eye infections is Staphylococcus aureus. Staphylococcus aureus generally affects adults more often than children Although rarely causes severe complaints, bacterial conjunctivitis can interfere with daily activities such as work or school. Bacterial conjunctivitis usually resolves on its own within 7 days but may continue for up to 2 weeks. Prescribing antibiotics in bacterial conjunctivitis can reduce complaints in patients and can also speed up healing. Selection of the right antibiotic is very important in order to obtain the desired treatment results. Chloramphenicol and levofloxacin are antibiotics with a broad spectrum that can be an option for the treatment of bacterial conjunctivitis caused by Staphylococcus aureus bacteria.